Teaching as Abductive Reasoning: The Role of Argumentation - Rapanta, Chrysi (Informal Logic, 2018)
The view that argumentation is a desired reasoning practice in the classroom is well reported in the literature. Nonetheless, it is still not clear what type of reasoning supports classroom argumentation. The paper discusses abductive reasoning as the most adequate for students’ arguments to emerge in a classroom discussion. Abductive reasoning embraces the idea of plausibility and defeasibility of both the premises and the conclusion. As such, teachers’ role becomes the one of guiding students through formulating relevant hypotheses and selecting the most plausible one according to criteria. Argumentation schemes are proposed as useful tools in this process.